1999
DOI: 10.1007/s004040050260
|View full text |Cite
|
Sign up to set email alerts
|

Importance of surgical margins in conization for cervical intraepithelial neoplasia grade III

Abstract: We conducted a retrospective study on 201 conizations for CIN III done over the last 14 years. Of these, 53 (26.4%) had involvement of the margins, 114 (56.7%) had margins free of neoplasia, and 34 (16.9%) were not evaluated. Of the 53 cases with margin involvement, 28 (52.8%) had complementary surgery and 25 (47.2%) cytological follow-up. Residual CIN was identified in the surgical specimen in 15 cases (53.6%) and microinvasion was present in 2 cases (7.1%). Of the 114 patients with margins free of neoplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 14 publications
0
18
0
3
Order By: Relevance
“…In a previous report, 38% of women with positive endocervical LEEP margins had residual disease detected at hysterectomy [15]. Patients with negative LEEP margins were also reported to recur [16], but recurrence rates were 4 times higher when the surgical margins were positive when compared with negative margins [17]. On the other hand, Livasy et al [8] reported no difference in recurrence rates of patients with and without positive margins.…”
Section: Discussionmentioning
confidence: 87%
“…In a previous report, 38% of women with positive endocervical LEEP margins had residual disease detected at hysterectomy [15]. Patients with negative LEEP margins were also reported to recur [16], but recurrence rates were 4 times higher when the surgical margins were positive when compared with negative margins [17]. On the other hand, Livasy et al [8] reported no difference in recurrence rates of patients with and without positive margins.…”
Section: Discussionmentioning
confidence: 87%
“…Tissue destroyed by LEEP and hemostatic cauterization could contribute to a lower recurrence rate [19]. Nevertheless, free lesion margins do not exclude recurrence [5,20]. A controversy exists regarding the use of a second loop during the surgical procedure in more severe lesions with a nonvisible squamous cervical junction [6].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have identified margin status, endocervical extension, and multiquadrant disease as risk factors for recurrence [4]. Margin status is the risk factor investigated most frequently [5,6]. Livasy et al [7] reported a recurrence rate of 39% in women with positive margins after LEEP, compared with 15% in women with negative margins.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the micronucleus test has been considered to be a very useful biomarker for detecting malignancy in the uterine cervix, with regard to other factors like surgical margins and the numbers of mitoses and methylated genes, for predicting recurrence of CIN III. [44][45][46] The number of micronuclei correlates with the severity of genetic damage. Cells containing several micronuclei present greater genetic damage than do cells that present only one micronucleus.…”
Section: Referencesmentioning
confidence: 99%